The Presence of the Metropolitan Sikuri in the Protests of November 2020 and Two of its Melodies - Serrano Finetti, Francisco Javier (2022)
This article provides a brief description of the practice of siku and its “artivism” during the demonstrations that occurred in Lima during the month of November 2020. The transcription and analysis of two musical products of their activity will be carried out. The scores below will also allow us to appreciate the melodic movement of the voice (similar to that performed by the sikus) and the bass drums. The lyrics will shed light on the values they transmit in their speech and the musical analysis will give an idea of how they manage to keep the attention of the listening public if we consider some characteristics of the instrument.